THE CONTRIBUTION OF AVICENNA TAJIK STATE MEDICAL UNIVERSITY EMPLOYEES TO THE VICTORY IN THE GREAT PATRIOTIC WAR (ON THE 75th ANNIVERSARY OF THE VICTORY) - M.K. GULOV; N.S. JURAEVA; A.K. BARATOV (Avicenna Tajik State Medical University, 2020)
The article is dedicated to the employees' memory of the Avicenna Tajik State Medical University, who took an active part in the Great Patriotic War. The heroic feat of the entire of Soviet people and, in particular, the medical workers - alumnus and the employees of Avicenna Tajik State Medical University - allowed to win a great Victory in the most terrible and murderously war in the whole of the history of humanity. The article, devoted to the 75th anniversary of the Victory, provides the names and brief biographical data of the majority of graduates and employees of Avicenna Tajik State Medical University. The bright memory of their heroic feat will remain forever in our hearts.